Sulfide solid electrolyte and preparation method and application thereof

By distributed single sulfur powder on the surface of lithium sulfide powder and mixed with other compounds with sintering, the problem of sulfide solid electrolytes volatilized during the high temperature sintering process, realized the preparation of pure phase electrolyte and the improvement of high ion conductivity rate , And further improve the performance of the full solid battery.

CN119370867APending Publication Date: 2025-01-28ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411508100.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When preparing sulfide solid electrolyte, the S element will evaporate during long-term high-temperature sintering, resulting in the generation of impurities in the sulfide solid electrolyte and reduce its ionic conductivity.

Method used

By distributed monocular sulfur powder on the surface of the lithium sulfide powder, a composite powder is formed, and sintering is performed after mixing with phosphorus and lithium halide to ensure the formation of electrolyte during the sintering process to avoid sulfur deletion and miscellaneous occurrence.

Benefits of technology

This method can obtain a pure phase sulfide solid electrolyte, improve its ionic conductivity, and then improve the electrochemical properties of a full solid -state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370867A_ABST
    Figure CN119370867A_ABST
Patent Text Reader

Abstract

The invention relates to a sulfide solid electrolyte and a preparation method and application thereof, and the preparation method comprises the following steps: distributing elemental sulfur powder on the surface of lithium sulfide powder to obtain composite powder; mixing the composite powder with phosphorus sulfide and lithium halide to obtain a precursor; and sintering the precursor to obtain the sulfide solid electrolyte. According to the preparation method disclosed by the invention, the elemental sulfur powder is distributed on the surface of the lithium sulfide powder, so that the elemental sulfur powder can participate in formation of the sulfide solid electrolyte before volatilization in the sintering process, the prepared sulfide solid electrolyte does not have sulfur loss, and no impurity phase is generated in the sulfide solid electrolyte; therefore, the ionic conductivity of the sulfide solid-state electrolyte can be improved, and the electrochemical performance of an all-solid-state battery can be obviously improved when the sulfide solid-state electrolyte is used for assembling the all-solid-state battery; meanwhile, the preparation method is simple and efficient, and the obtained sulfide solid electrolyte is uniform in performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, in particular to a sulfide solid electrolyte and a preparation method and application thereof. Background Art

[0002] Different from traditional liquid lithium-ion batteries, the electrolyte of all-solid-state batteries exists in the form of solid electrolytes in the electrodes, which have the advantages of non-volatility, non-combustion and fast ion conduction. Among them, sulfide solid electrolytes are widely used due to their excellent ion conductivity. However, the preparation of sulfide solid electrolytes requires long-term high-temperature sintering. During the long-term high-temperature sintering process, the S element will volatilize and be lost, resulting in the formation of impurities in the sulfide solid electrolyte phase, thereby reducing the ionic conductivity of the sulfide solid electrolyte.

[0003] In this regard, in the prior art, the S element is supplemented during a long period of high-temperature sintering, for example, high-temperature sintering is performed in a sulfur-containing atmosphere, so as to achieve the effect of supplementing the S element. However, in actual application, the S element in the sulfur-containing atmosphere is difficult to diffuse into the interior of the accumulated powder, resulting in a significant difference in the performance of the inner and outer powders. Summary of the invention

[0004] Based on this, it is necessary to provide a sulfide solid electrolyte and a preparation method and application thereof to address the above problems. The preparation method can obtain a pure-phase sulfide solid electrolyte, thereby improving the ionic conductivity of the sulfide solid electrolyte.

[0005] A method for preparing a sulfide solid electrolyte comprises the following steps:

[0006] Distributing elemental sulfur powder on the surface of lithium sulfide powder to obtain composite powder;

[0007] The composite powder is mixed with phosphorus sulfide and lithium halide to obtain a precursor;

[0008] The precursor is sintered to obtain a sulfide solid electrolyte.

[0009] In one of the embodiments, the mass ratio of lithium sulfide powder to elemental sulfur powder in the composite powder is 1.856:1 to 8.56:1.

[0010] In one embodiment, the lithium sulfide powder has a D 50 The particle size is 1 μm to 30 μm, and the D 50 The particle size is 50nm~500nm.

[0011] In one embodiment, elemental sulfur powder is distributed on the surface of lithium sulfide powder by high-energy ball milling, wherein in the high-energy ball milling process, the ball-to-material ratio is 5:1 to 30:1, the ball milling speed is 500 rpm / min to 750 rpm / min, and the ball milling time is 5 h to 20 h.

[0012] In one embodiment, the lithium halide is selected from at least one of lithium bromide, lithium chloride, lithium iodide and lithium fluoride.

[0013] In one embodiment, the phosphorus sulfide is at least one of P2S3, P2S5, P4S4, P4S7, P4S9, and P4S6.

[0014] In one embodiment, the sintering is carried out under a protective atmosphere at a temperature of 350° C. to 560° C. for a time of 5 h to 20 h.

[0015] A sulfide solid electrolyte obtained by the preparation method.

[0016] An all-solid-state battery, wherein the all-solid-state battery uses the sulfide solid electrolyte.

[0017] An electrical device using the all-solid-state battery.

[0018] In the preparation method of the present invention, elemental sulfur powder is distributed on the surface of lithium sulfide powder, so that during the sintering process, the elemental sulfur powder can participate in the formation of the sulfide solid electrolyte before volatilization, so that the prepared sulfide solid electrolyte will not have sulfur deficiency, and no impurities are generated in the sulfide solid electrolyte, thereby improving the ionic conductivity of the sulfide solid electrolyte. Furthermore, the use of the sulfide solid electrolyte of the present invention to assemble an all-solid-state battery can significantly improve the electrochemical performance of the all-solid-state battery.

[0019] In addition, the preparation method of the present invention is not only simple, efficient and low-cost, but also the obtained sulfide solid electrolyte has uniform performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 The XRD pattern of the sulfide solid electrolyte prepared in Example 1;

[0022] Figure 2The XRD pattern of the sulfide solid electrolyte prepared in Example 2;

[0023] Figure 3 This is the XRD pattern of the sulfide solid electrolyte prepared in Example 3;

[0024] Figure 4 This is the XRD pattern of the sulfide solid electrolyte prepared in Example 4;

[0025] Figure 5 This is the XRD spectrum of the sulfide solid electrolyte prepared in Comparative Example 1;

[0026] Figure 6 This is the XRD spectrum of the sulfide solid electrolyte prepared in Comparative Example 2;

[0027] Figure 7 This is the XRD spectrum of the sulfide solid electrolyte prepared in Comparative Example 3. DETAILED DESCRIPTION

[0028] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0030] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0031] The method for preparing the sulfide solid electrolyte provided by the present invention comprises the following steps:

[0032] S1, distributing elemental sulfur powder on the surface of lithium sulfide powder to obtain composite powder;

[0033] S2, mixing the composite powder with phosphorus sulfide and lithium halide to obtain a precursor;

[0034] S3, sintering the precursor to obtain a sulfide solid electrolyte.

[0035] In the preparation method of the present invention, elemental sulfur powder is pre-distributed on the surface of lithium sulfide powder, so that during the sintering process, the elemental sulfur powder can participate in the formation of the sulfide solid electrolyte before volatilization, so that the prepared sulfide solid electrolyte will not have sulfur deficiency, and no impurities are generated in the sulfide solid electrolyte, thereby improving the ionic conductivity of the sulfide solid electrolyte.

[0036] Specifically, there are many ways to distribute the elemental sulfur powder on the surface of the lithium sulfide powder in step S1, and the present invention is not limited to this. All ways that can distribute the elemental sulfur powder on the surface of the lithium sulfide powder can achieve the same effect; in addition, the present invention is not limited to the distribution method of the elemental sulfur powder on the surface of the lithium sulfide powder. The elemental sulfur powder can be randomly distributed on the surface of the lithium sulfide powder, or it can completely cover the sulfide powder to form a core-shell structure.

[0037] Since the ball milling process is simple and has good effects, as an example, in actual production, ball milling can be used to achieve pre-distribution of elemental sulfur powder on the surface of lithium sulfide powder. The ball milling method can be high-energy ball milling, low-energy ball milling or ordinary ball milling. Among them, high-energy ball milling not only has better dispersion effect, but also can make the lithium sulfide powder amorphous and produce an amorphous structure on the surface. Since the crystal growth of the sulfide solid electrolyte will be carried out around the lithium sulfide powder, the amorphous structure produced on the surface of the lithium sulfide powder is conducive to making the reaction during the sintering process more complete.

[0038] Therefore, the present invention preferably uses high-energy ball milling to distribute elemental sulfur powder on the surface of lithium sulfide powder, wherein in the high-energy ball milling process, the ball-to-material ratio is preferably 5:1-30:1, including but not limited to 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1, more preferably 15:1-20:1, and the ball milling speed is preferably 500 rpm / min The ball milling time is preferably 5h to 20h, including but not limited to 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, and is further preferably 5h to 10h.

[0039] The higher the purity of lithium sulfide powder and elemental sulfur powder, the better the performance of the prepared sulfide solid electrolyte and the higher the ionic conductivity. Therefore, the present invention preferably uses lithium sulfide powder with a purity greater than or equal to 99% and elemental sulfur powder with a purity greater than or equal to 99.99%.

[0040] In order to enable the elemental sulfur powder to fully replenish the sulfur loss in the preparation process of the sulfide solid electrolyte without any obvious residue, optionally, the mass ratio of lithium sulfide powder to elemental sulfur powder in the composite powder is 1.856:1 to 8.56:1, including but not limited to 1.856:1, 2.856:1, 3.856:1, 4.856:1, 5.856:1, 6.856:1, 7.856:1 or 1.856:1.

[0041] In order to effectively disperse the elemental sulfur powder on the surface of the lithium sulfide powder and promote the reaction kinetics of the raw material powder when preparing the sulfide solid electrolyte, the D 50 The particle size is preferably 1 μm to 30 μm, including but not limited to 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm or 30 μm, and is further preferably 3 μm to 5 μm. The D 50The particle size is 50nm to 500nm, including but not limited to 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm, The wavelength of the present invention is preferably 80nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm or 500nm, and more preferably 50nm to 200nm.

[0042] In step S2, when the composite powder is mixed with phosphorus sulfide and lithium halide, the mixing method is not limited, and mechanical mixing methods such as ball milling and mixing with a high-speed mixer are all possible, as long as the precursors are mixed evenly.

[0043] When mixed, the molar ratio of lithium sulfide to lithium halide and phosphorus sulfide in the composite powder satisfies the proportion of each element in the sulfide solid electrolyte, for example, Li 6-x PS 5-x A 1+x The proportion of each element in this type of argyrodite phase sulfide solid electrolyte, where A is selected from one or more of Cl, Br, I, and F, and 0≤x≤1.7.

[0044] Among them, the lithium halide is selected from at least one of lithium bromide, lithium chloride, lithium iodide, and lithium fluoride, the moisture content is preferably below 0.3%, the purity is preferably above 99%, and the physical state can be crystal or powder; the phosphorus sulfide is at least one of P2S3, P2S5, P4S4, P4S7, P4S9, and P4S6, preferably P2S5.

[0045] In step S3, the sintering is carried out under a protective atmosphere, and the protective atmosphere is selected from at least one of nitrogen, argon, etc., wherein the sintering temperature is preferably 350°C to 560°C, including but not limited to 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or 560°C, further preferably 420°C to 500°C, and the sintering time is preferably 5h to 20h, including but not limited to 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, further preferably 5h to 10h.

[0046] Since the present invention uses elemental sulfur powder to supplement sulfur elements, compared with high-temperature sintering in a sulfur-containing atmosphere, the present invention does not need to have excessively high requirements on the sealing of the carrier during high-temperature sintering, thereby reducing the process difficulty.

[0047] Therefore, the preparation method of the present invention is not only simple, efficient and low-cost, but also the obtained sulfide solid electrolyte has uniform performance.

[0048] The present invention also provides a sulfide solid electrolyte obtained by the preparation method. The sulfide solid electrolyte contains no impurities and has high ionic conductivity.

[0049] The present invention also provides an all-solid-state battery, which uses the sulfide solid electrolyte.

[0050] Since the sulfide solid electrolyte of the present invention has high ionic conductivity, the electrochemical performance of the all-solid-state battery can be significantly improved by assembling the all-solid-state battery using the sulfide solid electrolyte of the present invention.

[0051] The present invention also provides an electrical device, which is a vehicle, a mobile electronic device, etc. The electrical device uses the all-solid-state battery, so that the electrical device has higher safety and endurance.

[0052] For example, the energy density of liquid lithium-ion batteries using a high-nickel positive electrode and a silicon-based negative electrode system is only 350Wh / kg, which is close to the limit energy density. The all-solid-state battery using the sulfide solid electrolyte of the present invention can adapt to higher capacity positive and negative electrode materials, and the energy density can reach 500Wh / kg. The cruising range of vehicles equipped with all-solid-state batteries can easily reach 1,000km.

[0053] Hereinafter, the sulfide solid electrolyte and its preparation method and application will be further described through the following specific examples.

[0054] Example 1

[0055] Weigh D 50 32.78g of lithium sulfide with a particle size of 3μm, D 50 5.25 g of elemental sulfur powder with a particle size of 80 nm was placed in a zirconia vacuum ball mill, and 570 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. They were first mixed at a speed of 150 rpm for 1 hour, and then high-speed ball milled at a speed of 500 rpm for 5 hours to obtain a composite powder.

[0056] After the ball milling is completed, 41.73 g of phosphorus pentasulfide (P2S5) and 25.47 g of anhydrous lithium chloride are weighed and placed in a ball mill, mixed with the composite powder, and continued to ball mill at a rotation speed of 500 rpm for 5 hours to obtain a precursor.

[0057] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 460°C, and a sintering time of 15h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 Cl 1.6 .

[0058] Example 2

[0059] Weigh D 50 32.78g of lithium sulfide with a particle size of 1μm, D 50 10.5 g of elemental sulfur powder with a particle size of 150 nm was placed in a zirconia vacuum ball mill, and 570 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. The mixture was first mixed at a speed of 150 rpm for 1 h, and then high-speed ball milled at a speed of 500 rpm for 5 h to obtain a composite powder.

[0060] After the ball milling is completed, 41.73 g of phosphorus pentasulfide (P2S5) and 25.47 g of anhydrous lithium chloride are weighed and placed in a ball mill, mixed with the composite powder, and continued to ball mill at a rotation speed of 500 rpm for 5 hours to obtain a precursor.

[0061] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 460°C, and a sintering time of 15h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 Cl 1.6 .

[0062] Example 3

[0063] Weigh D 5032.78g of lithium sulfide with a particle size of 5μm, D 50 5.25 g of elemental sulfur powder with a particle size of 200 nm was placed in a zirconia vacuum ball mill, and 570 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. They were first mixed at a rotation speed of 150 rpm for 1 hour, and then high-speed ball milled at a rotation speed of 500 rpm for 10 hours to obtain a composite powder.

[0064] After the ball milling is completed, 41.73 g of phosphorus pentasulfide (P2S5) and 25.47 g of anhydrous lithium chloride are weighed and mechanically mixed with the composite powder at a speed of 20,000 rpm for 2 min to obtain a precursor.

[0065] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 480°C, and a sintering time of 10 h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 Cl 1.6 .

[0066] Example 4

[0067] Weigh D 50 27.84 g of lithium sulfide with a particle size of 1 μm, D 50 5.25 g of elemental sulfur powder with a particle size of 50 nm was placed in a zirconia vacuum ball mill, and 660 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. They were first mixed at a rotation speed of 150 rpm for 1 hour, and then ball-milled at a rotation speed of 500 rpm for 10 hours to obtain a composite powder.

[0068] After the ball milling is completed, 37.41 g of phosphorus pentasulfide (P2S5), 14.27 g of anhydrous lithium chloride, and 20.46 g of anhydrous lithium bromide are weighed and mixed with the composite powder for mechanical mixing at a speed of 20,000 rpm for 10 h to obtain a precursor.

[0069] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 440°C, and a sintering time of 10 h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 ClBr 0.7 .

[0070] Comparative Example 1

[0071] Weigh D 5032.78 g of lithium sulfide with a particle size of 5 μm was placed in a zirconia vacuum ball mill, and 490 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. They were first mixed at a rotation speed of 150 rpm for 1 hour, and then high-speed ball milled at a rotation speed of 500 rpm for 5 hours.

[0072] After the ball milling is completed, 41.73 g of phosphorus pentasulfide (P2S5) and 25.47 g of anhydrous lithium chloride are weighed and mechanically mixed with the ball-milled powder at a speed of 20,000 rpm for 2 min to obtain a precursor.

[0073] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 480°C, and a sintering time of 10 h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 Cl 1.6 .

[0074] Comparative Example 2

[0075] Weigh D 50 27.84 g of lithium sulfide with a particle size of 1 μm was placed in a zirconia vacuum ball mill, and 556 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. They were first mixed at a rotation speed of 150 rpm for 1 hour, and then high-speed ball milled at a rotation speed of 500 rpm for 10 hours.

[0076] After the ball milling is completed, 37.41 g of phosphorus pentasulfide (P2S5), 14.27 g of anhydrous lithium chloride, and 20.46 g of anhydrous lithium bromide are weighed and mechanically mixed with the ball-milled powder at a speed of 20,000 rpm for 2 min to obtain a precursor.

[0077] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 440°C, and a sintering time of 10 h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 ClBr 0.7 .

[0078] Comparative Example 3

[0079] Weigh D 50 32.78 g of lithium sulfide with a particle size of 5 μm was placed in a zirconia vacuum ball mill, and 490 g of zirconia balls with a diameter of 5 mm were weighed and placed in the ball mill. They were first mixed at a rotation speed of 150 rpm for 1 hour, and then high-speed ball milled at a rotation speed of 500 rpm for 5 hours to obtain a composite powder.

[0080] After the ball milling is completed, 5.25 g of elemental sulfur powder with a particle size of 200 nm, 41.73 g of phosphorus pentasulfide (P2S5), and 25.47 g of anhydrous lithium chloride are weighed and mechanically mixed with the ball-milled powder at a speed of 20,000 rpm for 2 min to obtain a precursor.

[0081] The precursor was sintered in a box furnace with nitrogen, with a heating rate of 2.5°C / min, a sintering temperature of 480°C, and a sintering time of 10 h. After crushing, D 50 Sulfide solid electrolyte Li with a particle size of 13 μm 5.4 PS 4.4 Cl 1.6 .

[0082] Test Example 1

[0083] The sulfide solid electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested for ionic conductivity. The ionic conductivity test method is as follows: the sulfide solid electrolyte samples obtained in the Examples / Comparative Examples were subjected to uniaxial press forming in a glove box filled with an inert atmosphere, and sheets with a diameter of 10 mm and a thickness of about 2 mm to 3 mm were manufactured at 200 MPa for testing, wherein the test was performed at room temperature (25° C.) using an electrochemical workstation and an AC impedance method under the conditions of a measurement frequency of 1 Hz to 7 MHz. The test results are shown in Table 1.

[0084] Table 1

[0085] Ionic conductivity (mS / cm) Example 1 11 Example 2 12.5 Example 3 10.3 Example 4 14.6 Comparative Example 1 8.1 Comparative Example 2 9.3 Comparative Example 3 8.4

[0086] It can be seen from Table 1 that the preparation method of the present invention can significantly improve the ionic conductivity of the sulfide solid electrolyte.

[0087] In addition, the sulfide solid electrolytes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were analyzed by XRD patterns. Figure 1 to Figure 7 As shown. Among them, from Figure 1 to Figure 4 It can be seen that by ball-milling the elemental sulfur powder and lithium sulfide in advance, the elemental sulfur powder is distributed on the surface of the lithium sulfide powder, and the sintered sulfide solid electrolyte presents a single argyrodite peak, with no impurity peaks at around 2θ=29°, 34°, and 35°, thus having high ionic conductivity; Figure 5 and Figure 6 It can be seen that in Comparative Examples 1 and 2, no elemental sulfur powder is added. Although the sintered sulfide solid electrolyte presents the characteristic peaks of argyrodite, there are also peaks of other impurities at around 2θ=29°, 34°, and 35°. This is attributed to the volatilization of sulfur element during the sintering process, which reduces the ionic conductivity of the sulfide solid electrolyte. Figure 7It can be seen that although the elemental sulfur powder of Comparative Example 3 can play a role in supplementing sulfur, the elemental sulfur powder at this time is randomly distributed, rather than distributed around the lithium sulfide powder, which will cause the elemental sulfur powder to volatilize rapidly when the temperature gradually increases, and cannot effectively participate in the formation of the sulfide solid electrolyte. Figure 7 There are also peaks of other impurities at around 2θ=29°, 34°, and 35°, which reduce the ionic conductivity of the sulfide solid electrolyte.

[0088] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0089] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a sulfide solid electrolyte, characterized in that: The following steps are involved: Distributing elemental sulfur powder on the surface of lithium sulfide powder to obtain composite powder; The composite powder is mixed with phosphorus sulfide and lithium halide to obtain a precursor; The precursor is sintered to obtain a sulfide solid electrolyte.

2. The method for preparing a sulfide solid electrolyte according to claim 1, characterized in that: The mass ratio of lithium sulfide powder to elemental sulfur powder in the composite powder is 1.856:1 to 8.56:

1.

3. The method for preparing a sulfide solid electrolyte according to claim 1, characterized in that: The D of the lithium sulfide powder 50 The particle size is 1 μm to 30 μm, and the D 50 The particle size is 50nm~500nm.

4. The method for preparing a sulfide solid electrolyte according to claim 1, characterized in that: The elemental sulfur powder is distributed on the surface of the lithium sulfide powder by high-energy ball milling, wherein in the high-energy ball milling process, the ball-to-material ratio is 5:1-30:1, the ball milling speed is 500rpm / min-750rpm / min, and the ball milling time is 5h-20h.

5. The method for preparing a sulfide solid electrolyte according to claim 1, characterized in that: The lithium halide is selected from at least one of lithium bromide, lithium chloride, lithium iodide and lithium fluoride.

6. The method for preparing a sulfide solid electrolyte according to claim 1, characterized in that: The phosphorus sulfide is at least one of P2S3, P2S5, P4S4, P4S7, P4S9, and P4S6.

7. The method for preparing a sulfide solid electrolyte according to claim 1, characterized in that: The sintering is carried out under a protective atmosphere at a temperature of 350° C. to 560° C. for a time of 5 h to 20 h.

8. A sulfide solid electrolyte obtained by the preparation method according to any one of claims 1 to 7.

9. An all-solid-state battery, characterized in that: The all-solid-state battery uses the sulfide solid electrolyte as claimed in claim 8.

10. An electrical device, characterized in that: The electrical equipment uses the all-solid-state battery as claimed in claim 9.

Citation Information

Cited By

  • Solid-state battery and preparation method thereof

    CN120809938A

  • Lithium-sulfur-phosphorus-chlorine-bromine solid electrolyte, preparation method thereof and all-solid-state battery

    CN121292383A

  • A lithium-sulfur-phosphorus-chloro-bromine solid electrolyte, its preparation method, and an all-solid-state battery

    CN121292383B